ANALISIS SISTEM KOMPENSASI MENGGUNAKAN METODE ADHERED PADA UKM ABEL LAUNDRY - Muhammad Zaki; Akmal Hidayat Winarto; Najwa Nuria Shadrina; Mesza Azaria Namora (Jurnal Pijar, 2026)
Many SMEs still face challenges in managing human resources, particularly in implementing fair and standardized compensation systems. This study aims to analyze the compensation system at Abel Laundry SME in Solo City using the adhered and compare it with the Provincial Minimum Wage (UMP) of Central Java and the City Minimum Wage (UMK) of Surakarta. The research was conducted using primary data obtained through in-depth interviews with the business owner. The analysis was carried out through a salary survey, job evaluation using compensable factors, and salary mapping using the adhered method. The results indicate that before the evaluation, most employee salaries were still below the Surakarta UMK and the salary structure was not yet well organized. After the improvement using the adhered approach, the salary structure became more systematic, proportional, and aligned with job values. This improvement also increased the company’s total salary expenditure but created a fairer compensation structure that can potentially enhance employee motivation and welfare.